STRATEGI KOMUNIKASI PEMASARAN WISATA BAHARI: STUDI KASUS PULAU CAMBA-CAMBANG PANGKEP - Ridha Amaliyah (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2025)
This research to analyse the marketing communication strategy of marine tourism on Camba-Cambang Island, Pangkep Regency, and to identify the supporting and inhibiting factors in its implementation. Employing a descriptive qualitative approach, data were collected through interviews, observations, and documentation involving the Tourism Office, destination managers, and visitors. The findings reveal that the marketing communication strategy has been implemented through a promotion mix consisting of advertising, sales promotion, personal selling, and direct marketing. However, its effectiveness remains limited due to weak digital innovation, accessibility constraints, and the absence of strong branding. An analysis using the AIDDA model demonstrates that promotion efforts only reach the stages of attracting attention (attention) and interest (interest), but have yet to effectively stimulate desire (desire), decision (decision), and actual action (action) among tourists. Supporting factors include the island’s strategic location and the availability of continually improved facilities, while inhibiting factors consist of limited human resources, unpredictable weather, and lack of creativity in digital promotion. This study highlights the need for more innovative and collaborative marketing communication strategies, involving local communities and stakeholders, to strengthen the competitiveness of Camba-Cambang Island as a sustainable marine tourism destination